2018
DOI: 10.1111/1462-2920.14450
|View full text |Cite
|
Sign up to set email alerts
|

Rapidly mitigating antibiotic resistant risks in chicken manure by Hermetia illucens bioconversion with intestinal microflora

Abstract: Summary Antibiotic resistance genes (ARGs) in animal manure are an environmental concern due to naturally occurring bacteria being exposed to these wastes and developing multidrug resistance. The bioconversion of manure with fly larvae is a promising alternative for recycling these wastes while attenuating ARGs. We investigated the impact of black soldier fly (BSF, Hermetia illucens) larval bioconversion of chicken manure on the persistence of associated ARGs. Compared with traditional composting or sterile la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 49 publications
(68 reference statements)
0
32
1
Order By: Relevance
“…The increased feed intake observed in the laying hens of present study can be attributed to the improvement of the diet palatability related to HILM (Bovera et al 2015;Cullere et al 2016). It is possible to assume that the improvement of production performance is related to the improvement of metabolism, immunity and intestinal health (Cutrignelli et al 2018;Cai et al 2018;Sypniewski et al 2020). However, Schiavone et al (2018) showed that 50% or 100% replacement of soybean oil with HILM in broiler chickens diets has no adverse effects on the daily feed intake or feed conversion ratio.…”
Section: Discussionmentioning
confidence: 55%
“…The increased feed intake observed in the laying hens of present study can be attributed to the improvement of the diet palatability related to HILM (Bovera et al 2015;Cullere et al 2016). It is possible to assume that the improvement of production performance is related to the improvement of metabolism, immunity and intestinal health (Cutrignelli et al 2018;Cai et al 2018;Sypniewski et al 2020). However, Schiavone et al (2018) showed that 50% or 100% replacement of soybean oil with HILM in broiler chickens diets has no adverse effects on the daily feed intake or feed conversion ratio.…”
Section: Discussionmentioning
confidence: 55%
“…Second, due to exposure to heavy metals and antibiotics in the environment (especially in pig manure), there have been many studies on heavy metals and antibiotics in H . illucens [4547].…”
Section: Discussionmentioning
confidence: 99%
“…Wynants et al (2018) studied BSFL rearing with a variety of mostly grain-based substrates in several laboratory and industry-scale settings, Jiang et al (2019) with food waste in an industry-scale setting, and Bruno et al (2019) with a standard substrate for fly rearing, vegetables and fish waste in a laboratory setting ( Table 3). Considering that substrate digestion by BSFL (Cai et al, 2018;Bruno et al, 2019) and other fly larvae (e.g., Lucilia sericata, Diptera: Calliphoridae) (Mumcuoglu et al, 2001;Lerch et al, 2003) decreases bacterial richness along the digestive tract (Gold et al, 2018;Vogel et al, 2018), different feeding rates, intervals, and larval densities among studies could be especially relevant ( Table 3). One could expect that the substrate and residue bacterial community is altered to a greater extent by BSFL when less feed is provided per larvae (i.e., lower feeding rate and/or higher larval density).…”
Section: Common Fly Associated Bacteria Dominate the Rearing Residuementioning
confidence: 99%
“…Jiang et al (2019) were the first to determine bacterial community dynamics throughout one rearing cycle and found that BSFL rearing affects and alters the substrate bacterial community over time to increase the capacity to decompose the substrate. Lalander et al (2013) and Erickson et al (2004) also reported a reduction in certain bacteria during BSFL rearing, and Cai et al (2018) and Liu et al (2020) reported a reduction in antibiotic resistance genes in bacteria. These results contradict the findings of Bruno et al (2019), who did not identify a significant influence of BSFL on substrate microbiota during rearing.…”
Section: Introductionmentioning
confidence: 96%